2008
DOI: 10.1002/anie.200705537
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Growth of Charged‐Nanoparticle Chains through Interparticle Electrostatic Repulsion

Abstract: Nanoparticles (NPs) are envisaged as both building blocks to form advanced materials [1][2][3] and appropriate models to gain insight into condensed-matter physics; [4][5][6][7] this is because of their unique dimensions and the innovative physical properties derived thereof. All these promising applications of the NPs are primarily dependent on the capability of controlling their spatial coupling. Self-assembly of NPs is driven by various forces, such as van der Waals interactions, which lead to either dense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
263
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(274 citation statements)
references
References 20 publications
8
263
1
1
Order By: Relevance
“…It has been widely investigated that self-assembly is controlled by attractive forces such as van der Waals force, hydrogen bonding and repulsive forces such as steric repulsion and electrostatic repulsion. [40][41][42] When the reaction was performed for 1 h, the resulting products are self-assembled underdeveloped aggregated nanoplates with an average diameter of 1 mm, as shown in Fig. 4a, while the inset displays the high magnication FESEM image of a single nanoplate.…”
Section: Formation Mechanismmentioning
confidence: 99%
“…It has been widely investigated that self-assembly is controlled by attractive forces such as van der Waals force, hydrogen bonding and repulsive forces such as steric repulsion and electrostatic repulsion. [40][41][42] When the reaction was performed for 1 h, the resulting products are self-assembled underdeveloped aggregated nanoplates with an average diameter of 1 mm, as shown in Fig. 4a, while the inset displays the high magnication FESEM image of a single nanoplate.…”
Section: Formation Mechanismmentioning
confidence: 99%
“…For the magnetic nanocomposite to be used as [20]. The worm-like morphology of the nanocomposite is due to the arrangement of magnetic component driven by electrostatic repulsion, van der Waals attraction, dipolar interaction, and charge-dipolar interaction [39,40], according to the Derjaguin-La ndau-Verwey-Overbeek (DLVO) theory [39]. Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…12B). [156,157] The role of electrostatic repulsion highlighted in Wang's work is twofold: firstly, although being isotropic, the electrostatic repulsion favors anisotropic rather than isotropic self-assembly of charged particles; secondly, it defines the sizes of the particle assemblies. Wang et al have also observed the rearrangement of the electric double layer of the charged nanoparticles to new uniform layer surrounding the whole nanoparticle chains.…”
Section: Molecular-mimetic Self-assembly Of Colloidal Particlesmentioning
confidence: 99%
“…Wang et al have also observed the rearrangement of the electric double layer of the charged nanoparticles to new uniform layer surrounding the whole nanoparticle chains. [156] Förster and co-workers have succeeded in directing self-assembly of CdSe/CdS core-shell nanoparticles, coated with a homogenous corona of hydrophilic polyethylene oxide brushes, into chains, branched network, and hollow spheres (colloidosomes) by simply lowering the grafting density of the polymer chains on the particles (Fig. 12C).…”
Section: Molecular-mimetic Self-assembly Of Colloidal Particlesmentioning
confidence: 99%
See 1 more Smart Citation